2022
DOI: 10.3390/ijerph19106028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Park-Based Physical Activity Intervention on Psychological Wellbeing at the Time of COVID-19

Abstract: Practicing regular physical activity in green spaces has been invocated as a promising strategy for improving wellbeing in urban settings. The aim of the study was to assess the effect of a structured park-based physical activity intervention, the “Moving Parks” project, on citizens’ wellbeing at the time of COVID-19. The intervention was carried out in six public parks in Bologna (Italy) and administered by qualified instructors (from May 2021 to September 2021). The Psychological General Well Being Index sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…In China, where urbanization is accelerating, the relationship between the health level and quality of life of urban residents and urban forest parks has become increasingly important [6], especially in the context of COVID-19, where the demand for parks and outdoor green spaces has increased rather than decreased [7]. Studies have shown that physical exercise in green spaces can release stress and enhance the body's ability to fight infectious diseases [7][8][9]. Therefore, it can be predicted that in the future, the demand for forest parks and exercise activities will continue to grow and more urban residents can benefit from the services of forests and parks [10].…”
Section: Introductionmentioning
confidence: 99%
“…In China, where urbanization is accelerating, the relationship between the health level and quality of life of urban residents and urban forest parks has become increasingly important [6], especially in the context of COVID-19, where the demand for parks and outdoor green spaces has increased rather than decreased [7]. Studies have shown that physical exercise in green spaces can release stress and enhance the body's ability to fight infectious diseases [7][8][9]. Therefore, it can be predicted that in the future, the demand for forest parks and exercise activities will continue to grow and more urban residents can benefit from the services of forests and parks [10].…”
Section: Introductionmentioning
confidence: 99%
“…Among the 10 studies employing real physical interventions, four involved participants in multiple sessions over an extended period. Specifically, one study featured a year-long community gardening program [24 ▪▪ ], another involved 3 months of physical activities in a park [25], a third comprised eight outdoor swimming sessions [26 ▪▪ ], and the final one encompassed thirty 3-h therapeutic gardening sessions spanning over 15 weeks [27 ▪▪ ]. All four of these studies were of high quality and consistently showcased a significant reduction in anxiety and depression upon completion of the intervention.…”
Section: Resultsmentioning
confidence: 99%
“… April 2020 Observational, cross-sectional, qualitative, online survey Investigate associations between current life satisfaction and spatial characteristics during COVID-19 Parks Total amount of park space Life satisfaction One open-ended question to describe aspects what participants are currently satisfied in their life Based on text mining analysis, for people living in the Western area, satisfaction with the circumstances surroundings parks was observed, however, for the Eastern and Central City area, there was a weak or no relationship observed. Toselli et al (2022) , Italy Adults and older adults (328, largest age group 18–44 years (46.7%), 77.1%, n.a.) May–September 2021 Experimental, longitudinal, quantitative, online survey Investigate the impact of a structured park-based physical activity intervention on well-being during COVID-19 Urban parks Three-month park-based exercise intervention Well-being Psychological General Well Being Index short form (PGWB-S) For women, psychological well-being improved across all six domains (feeling nervous, full of energy, downhearted, emotionally stable, cheerful, tired), whereas for men, improvements were only observed for two domains (feeling full of energy, feeling tired).…”
Section: A1 Detailed Search Strategy Implementedmentioning
confidence: 99%